Susceptibility of the hispid cotton rat (Sigmodon hispidus) to the Lyme disease spirochete (Borrelia burgdorferi) - Burgdorfer, W; Gage, K L (The American journal of tropical medicine and hygiene, 1987)
The susceptibility of the hispid cotton rat, Sigmodon hispidus, to the Lyme disease spirochete, Borrelia burgdorferi, was investigated by inoculating rats with infected tick suspensions or by allowing infected Ixodes scapularis nymphs to feed on them. Culture of blood samples in BSK II medium demonstrated that cotton rats developed spirochetemias that lasted for a minimum of 3 to 4 weeks and were of sufficient concentration to infect simultaneously feeding normal I. scapularis nymphs. The spirochetemias were characterized by alternating spirochete-positive and spirochete-negative phases similar to patterns caused by relapsing fever borreliae. The possibility that B. burgdorferi is subject to antigenic variations, as reported for the relapsing fever spirochete, B. hermsii, is suggested.